Efeito de parâmetros geométricos e operacionais sobre o comportamento do pó fluxante no molde de lingotamento contínuo de placas - Carlos Eduardo Passagli Barral (2006)
Fluid flow in continuous casting reactors, tundish and mould, has a significant effect on the product quality and can also limit the productivity that can be attained in the process. In the continuous casting mould, an increase in productivity is always associated to increases in the casting speed, in the liquid metal flowrate and consequently, in the levels of turbulence, particularly in the upper regions, near the interface between liquid steel and mould flux. These higher levels of turbulence can cause emulsification of the mold flux and lead to entrapment of non metallic particles in the liquid steel. The configuration of the submerged entry nozzle used to deliver liquid metal into the mould also plays a significant role in determining the levels of turbulence near the interface between liquid steel and mould flux. In the present work, the effects of the configurations of the submerged entry nozzle, of the properties of the mould flux and of the operational parameters of the continuous casting machine on the behaviors of the interface between liquid steel and mould flux and on the degree of emulsification of the mould flux have been studied using physical modeling. The physical model reproduced Usiminas N. 2 continuous caster, in a 1:3 scale. The model was completely transparent to enable the visualization of the interface between liquid steel and mould flux. These two fluids were simulated by water and silicone oil, respectively. In the experiments with the physical model, the images of the interface between water and oil were recorded using a video camera. These images were post processed to determine the degree of emulsification of the oil. The velocity of the water near theinterface with the oil was also estimated and compared to prediction of a mathematical models. The results indicated that emulsification is caused by the turbulence in interface between water and oil (steel and mold flux). Among the parameters that were investigated, the penetration of the nozzle in the liquid and the angle of the ports presented the most significant effects on emulsification.